2016
DOI: 10.2214/ajr.15.15356
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy CT of Urate Deposits in Costal Cartilage and Intervertebral Disks of Patients With Tophaceous Gout and Age-Matched Controls

Abstract: DECT of the abdomen, chest wall, and spine revealed extensive MSU deposits in costal cartilages and, to a lesser extent, intervertebral disks in the male patients with gout in our study. These were quantified volumetrically. However, age-matched control subjects showed similar deposits, indicating this was not a disease-specific finding. Thus, MSU deposition in the axial skeleton may be physiologic in middle-aged men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Novel findings, using DECT, have further indicated that, in the absence of gout, urate crystals deposit in costal cartilages and intervertebral disks in middle-aged men [ 17 ], and at several sites of axial and peripheral joint involvement in spondyloarthropathy and seronegative rheumatoid arthritis patients [ 18 , 19 ]. Nevertheless, the mechanism and tissue effects of deposited urate crystals in these conditions are unknown.…”
Section: Urate Crystal Deposits Often Remain Clinically Silentmentioning
confidence: 99%
“…Novel findings, using DECT, have further indicated that, in the absence of gout, urate crystals deposit in costal cartilages and intervertebral disks in middle-aged men [ 17 ], and at several sites of axial and peripheral joint involvement in spondyloarthropathy and seronegative rheumatoid arthritis patients [ 18 , 19 ]. Nevertheless, the mechanism and tissue effects of deposited urate crystals in these conditions are unknown.…”
Section: Urate Crystal Deposits Often Remain Clinically Silentmentioning
confidence: 99%
“…Lastly, gout is known to most frequently affect the first metatarsophalangeal joint, but it can involve other parts of the body. 10 11 With the advantage of DECT scans allowing to analyse multiple joint sites within the entire foot in a single scan, we were able to find MSU crystal deposits outside the metatarsophalangeal joints.…”
Section: Discussionmentioning
confidence: 96%
“…Carr et al found strong DECT signal intensity indicating MSU deposition in the costal cartilages and intervertebral disks of patients with chronic gout but interestingly also found similar findings in healthy age-matched male control subjects, but not young control subjects. 46 The findings suggest that physiologic MSU deposition may occur in these regions in middle-aged and older men.…”
Section: Dual-energy Computed Tomographymentioning
confidence: 88%